Getting work done : prioritize your work, be more efficient, take control of your time. - Thomas, James Edward (20 minute manager series., 2022)
Overwhelmed by the sheer volume of work you need to accomplish? Being pulled in different directions by competing priorities? Getting Work Done runs you through the basics of being more productive at work. You'll learn to: - Align your schedule with your priorities - Focus your attention and avoid distractions - Create effective daily routines - Set boundaries and learn to say no Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly listen to and apply, for ambitious professionals and aspiring executives-from the most trusted source in business.